Length Weight Analysis and Condition Factors of Cork Fish (Channa Striata) Caught in Belanti Swamp, Ogan Komering Ilir District - Helmizuryani Helmizuryani; Meika Puspita Sari; Elva Dwi Harmilia; Irkhamiawan Ma'ruf; Widya Yolanda (Journal of Global Sustainable Agriculture, 2025)
Belanti village used to be land before the entry of the palm oil company, which caused the canalization to form a lake or swamp. The company's canalization blocked the flow of a natural river in Ulak Pati, Pampangan sub-district, preventing water from flowing and causing it to pool in what was once open land. The result of this canalization caused changes to the ecosystem in the village of Rawa Belanti, which had an impact on the growth factors of aquatic organisms that formed along with the formation of the lake/swamp. This study focuses on collecting data and information about the growth of cork fish that are found in many communities in rawa belanti through the sampling method. The study was conducted for 4 months with sampling intervals every 10 days. Calculation of length-weight and condition factor used all cork fish caught during the sampling.The growth factors assessed were the correlation between length and weight, and the condition factor of the gourami fish caught in the swamp. Based on the results of the study, the correlation of length and weight growth is negative allometric, which means that weight growth is slower than the growth of fish length. Assessment of the condition factor of cork fish shows an average value of 1, which means that the fish is in good body condition. Water quality assessment was also conducted in order to support growth data.